Impacts of changes in climate and land cover-land use on flood characteristics in Gorganrood Watershed (Northeastern Iran) during recent decades*. Issue 4 (2nd October 2018) - Irannezhad, Masoud; Minaei, Masoud; Ahmadian, Saghar; Chen, Deliang
ABSTRACT: This study evaluated the effects of changes in climate and land cover-land use (LCLU) on flood intensity and frequency in the Gorganrood Watershed (GW) located in the northeast of Iran during recent decades. For this purpose, hydroclimatic (precipitation, temperature, and river discharge) time series recorded at nine stations placed in the GW during 1973–2014 were used. Flood characteristics in terms of mean, maximum and number of peaks at five discharge stations (Galikash, Gonbad, Huji Ghushan, Tamar, and Tangrah) sited in the outlet of GW sub-basins were determined applying the Peak-Over-Threshold (POT) method to daily specific discharges. This is designed to remove the effect of the different size of sub-basins. The whole study period was divided into three 14-years segments (1973–1986, 1987–2000 and 2001–2014) based on satellite LCLU maps produced for 1973, 1986, 2000 and 2014. In the GW and its sub-basins during recent decades, both flood intensity and frequency increased, the climate became wetter and warmer, and LCLU mostly converted from rangeland to farmland. The partial correlation analyses identified that flood frequency in GW was primarily connected to the LCLU conversions, but moderately to observed wetter and warmer climate. Similarly, the Tamar sub-basin experienced effects of LCLU and climate on the maximum and the number of peaks. In Haji Ghushan, wetter and warmer climate resulted in more intense and frequent floods. Increases in precipitation appear to have played the most important role in the higher flood frequency in Galikash.